PHELAN, Mary; RUDVIN, Mette; SKAADEN, Hanne; and KERMIT, Patrick Stefan. Ethics in Public Service Interpreting. London & New York, Routledge, 2020, 206 pp., ISBN 978-1-138-88615-5 - López-Pelén, Eddie (Hikma, 2023)
.